Commercially available lipid formulations of amphotericin B: are they bioequivalent and therapeutically equivalent? - Cifani, C.; Costantino, S.; Massi, et al., M. (Acta Biomedica Atenei Parmensis, 2012)
Amphotericin B is a polyene macrolide derived from Streptomyces nodosus. Introduced into therapy in 1957, for decades amphotericin B has been the “gold standard” for fighting systemic fungal infections. In order to facilitate its systemic use, much attention has been paid to the development of pharmaceutical forms that could reduce its toxicity, especially for the kidney. Because of its low solubility in water and excellent solubility in lipids, amphotericin B is an ideal candidate for lipid-based formulations. Three different lipid formulations for intravenous infusion are currently commercially available: liposomal amphotericin (AmBisome®),Amphotericin lipid complex (Abelcet®) and Amphotericin colloidal dispersion (Amphocil®). The three lipid formulations of amphotericin B show significantly different structural, physical, chemical, pharmacokinetic, pharmacodynamic and toxicological characteristics. Several lines of evidence indicate that the three formulations of amphotericin B are not therapeutically equivalent. First, they are not bioequivalent. Second, even though a complete picture of controlled clinical research designed to compare effectiveness and safety of the three lipid formulations is not available, all the clinical studies analyzed report clear differences in toxicity between the three formulations. AmBisome® appears to be clearly less toxic than the other two formulations, in terms of nephrotoxicity and of incidence of infusion-related adverse events. Third, the therapeutic non-equivalence of the three lipid formulations of amphotericin B is further supported by statements of Conferences and Scientific Societies that in their recommendations have awarded different grading to the three lipid formulations.